Prevalence and molecular epidemiology of Staphylococcus aureus nasal colonization in four nursing home residents in Crete, Greece. Issue 2 (February 2020) - Moschou, A.; Maraki, S.; Giormezis, N.; Moraitaki, H.; Stafylaki, D.; Militsopoulou, M.; Spiliopoulou, I.; Papadakis, J.A.; Samonis, G.; Kofteridis, D.P.
Abstract: Nursing homes are considered as reservoirs for methicillin-resistant Staphylococcus aureus (MRSA). The present study investigated the point prevalence and molecular epidemiology of S. aureus colonization among nursing home residents. The study population comprised of 227 residents, living in four nursing homes of the Heraklion, Crete, Greece area, between January and December 2015. From each nursing home, swabs from the anterior nares of all eligible participants were obtained within a 2-week period. The isolated S. aureus strains were identified and screened by standard microbiological and molecular epidemiological methods. S. aureus carriage was found in 62 out of 227 participants (38.4%) with 33 out of 62 (53.2%) being MRSA. The median age was 83 years (range 52–103). Females were more frequently colonized [47 (75.8%)]. All 33 methicillin resistant Staphylococcus aureus (MRSA) isolates were mecA -positive carrying SCC mec type IV, 30 (91%) the fnbA, and 17 (51.5%) the PVL genes. Thirty-two (97%) belonged to a single pulsotype C; among them, the PVL-positives belonged to ST80 clone, whereas, the PVL-negatives to ST225. Among the 33 MRSA isolates, 32 (97%) were clindamycin-resistant, carrying the ermA gene. Methicillin-susceptible Staphylococcus aureus (MSSA) strains showed polyclonality and 76% were PVL-positive. In conclusion the present study has shown that nursing homes in our area can be regarded as important reservoirs for community-associated MRSA (CA-MRSA).